A Utilidade do disque-denúncia, enquanto serviço de registro de denúncias anônimas de maus tratos contra animais - MASSIH, Mirna Maia Abdul (2022)
The purpose of this study is to analyze the utility of the Hotline, as a service for registering anonymous complaints of ill-treatment against animals. In view of the recent legislative innovation brought by Law No. 14.064 / 2020, motivated by the increased visibility of the animal cause on social media and, consequent awareness of the population about the need to protect these beings, we sought to study the service, due to its main characteristic, the guarantee of the anonymity of the whistleblower, which consists in encouraging the communication of crime by this means.Through bibliographic and documentary research, the work was developed, based on the analysis of the service's functioning and the profile of anonymous reports of ill-treatment against animals, allegedly occurred in the municipality of Belém and in the Metropolitan Region, as well as the analysis responses recorded by the police authorities responsible for conducting investigative activities. From the data analysis, it was possible to conclude that the process of constituting the report of the complaint, based on the communication established between the complainant and the tele attendant, results in the provision of precise informational elements about the authorship, location and execution of the crime, able to subsidize a effective police diligence to verify the veracity of the complaint, however, the analysis of the treatment given to these complaints by the responsible police agents was impaired, due to the small amount of responses recorded in the Hotline system.